Pengaruh Kepemimpinan Kepala Sekolah dan Budaya Sekolah Terhadap Kinerja Guru TK - Rika Dwi Putri; Tri Widayatsih; Mahasir Mahasir (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study was conducted with the aim of analyzing and describing the influence of principals' leadership and school culture on teacher performance, either partially or simultaneously. To perform these tests, this research uses quantitative methods. Data collection techniques were carried out through questionnaires and documentation, and the data obtained were analyzed through multiple regression tests which first tested the normality distribution of the data, symptoms of heteroscedasticity and multicollinearity. The results obtained from the research conducted stated that the data were normally distributed, there were no symptoms of heteroscedasticity and multicollinearity so that the test was continued with parametric statistical analysis. So it can be concluded that the principal's leadership partially has a significant influence on teacher performance. Likewise, school culture has a significant influence on teacher performance in partial testing. In simultaneous testing, it was stated that the principal's leadership and school culture had a significant influence on the performance of kindergarten teachers in the Banyuasin III sub-district, Banyuasin Regency. Keywords : Principal Leadership, School Culture, Teacher Performance